Development of a new extraction technique and HPLC method for the analysis of non-psychoactive cannabinoids in fibre-type Cannabis sativa L. (hemp) - Brighenti, Virginia; Pellati, Federica; Steinbach, Marleen; Maran, Davide; Benvenuti, Stefania (Journal of pharmaceutical and biomedical analysis, 2017)
[Display omitted] •A new HPLC method for non-psychoactive cannabinoids analysis in hemp is proposed.•The fused-core stationary phase remarkably improved the HPLC performance.•The extraction procedure was optimized to obtain a high yield.•The method was fully validated in agreement with ICH guidelines.•Hemp inflorescences and derivatives were analysed for the content in cannabinoids. The present work was aimed at the development and validation of a new, efficient and reliable technique for the analysis of the main non-psychoactive cannabinoids in fibre-type Cannabis sativa L. (hemp) inflorescences belonging to different varieties. This study was designed to identify samples with a high content of bioactive compounds, with a view to underscoring the importance of quality control in derived products as well. Different extraction methods, including dynamic maceration (DM), ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE) and supercritical-fluid extraction (SFE) were applied and compared in order to obtain a high yield of the target analytes from hemp. Dynamic maceration for 45min with ethanol (EtOH) at room temperature proved to be the most suitable technique for the extraction of cannabinoids in hemp samples. The analysis of the target analytes in hemp extracts was carried out by developing a new reversed-phase high-performance liquid chromatography (HPLC) method coupled with diode array (UV/DAD) and electrospray ionization-mass spectrometry (ESI–MS) detection, by using an ion trap mass analyser. An Ascentis Express C18 column (150mm×3.0mm I.D., 2.7μm) was selected for the HPLC analysis, with a mobile phase composed of 0.1% formic acid in both water and acetonitrile, under gradient elution. The application of the fused-core technology allowed us to obtain a significant improvement of the HPLC performance compared with that of conventional particulate stationary phases, with a shorter analysis time and a remarkable reduction of solvent usage. The analytical method optimized in this study was fully validated to show compliance with international requirements. Furthermore, it was applied to the characterization of nine hemp samples and six hemp-based pharmaceutical products. As such, it was demonstrated to be a very useful tool for the analysis of cannabinoids in both the plant material and its derivatives for pharmaceutical and nutraceutical applications.